Comment on “Rapid Image Reconstruction of Structured Illumination Microscopy Directly in the Spatial Domain” and More About Point Spread Function Shaping for Enhanced Imaging Resolution - Dror Fixler; Zeev Zalevsky (IEEE Photonics Journal, 2021)
During the past several decades, a variety of imaging modalities in fluorescence microscopy have emerged as powerful tools for probing the spatial and temporal dimensions in fixed and living cells and tissues to uncover structural and dynamic information. Recently, our journal accepted a paper in this topic, and we received comments. We found it as opportunity to discuss this important topic for additional angles. We believe that this discussion will be interesting and helpful to the whole community.